Learning to Recognize The Names of Allah Through Problem-Based Learning Model in Elementary School - Hasanah Hasanah; Sunarti Sunarti (Universitas Tanjungpura, 2022)
This study aims to improve elementary school student's knowledge and understanding of the Names of Allah topic. Each individual or group does not know about Asmaul Husna. The material will be provided when starting the learning process from easy to difficult which is effectively integrated and becomes easier and real to accept and read, even memorize and preserve for days in the good life and not difficult to improve the ability and knowledge thoroughly and compatibly. Through cooperative learning method with a quantitative descriptive research approach Classroom Action Research (CAR) is a way of determining how to do it with cycles I to II, how to obtain this data is known as the data collection method. The participant in the the study was fourth graders, which amounted to 33 students in elementary school. In cycle I, 24 students passed with a percentage of 72%. Those who have not passed amounted to 9 students with a percentage of 28%. Then, in Cycle II with improved planning and implementation accurately using the problem based learning (PBL) model, the number of passed students was 33 students with a percentage of 100%.